Executive Committee Minutes 2022-02-24 - Academic Senate:::::::::
Agenda - Approved. Minutes for 2/10/ 22 - Approved. Chair Report. President Report. From EPC: Revision to the Education MA - Approved for Senate Agenda. Provost Report. Statewide Senator Report. Vice Chair Report. Resolution re: United in Kindness - Approved for the Senate agenda. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Modality for the Executive Committee for AY 22-23 - Approved for virtual AY 22-23. Special Report on Orientation for the Senate. Faculty Eligible for Emeritus Status and request for Distinguished Chair for Greg Sarris -Faculty Eligible for Emeritus Status approved for consent calendar, Request for Distinguished Chair Emeritus approved for the Senate agenda. From EPC: Memo about AB 928 - Endorsed by the Ex Com. Senate Agenda - Approved.